2020
DOI: 10.1109/access.2020.2978544
|View full text |Cite
|
Sign up to set email alerts
|

Quality Adaptation and Resource Allocation for Scalable Video in D2D Communication Networks

Abstract: Recently fifth-generation (5G) of cellular networks appeared to enable various smart bandwidth thirsty applications. Frequency re-usability via device-to-device (D2D) communication is one of the possible ways to enhance the 5G network throughput. However, despite these technological advancements in cellular networks, users' Quality of Experience (QoE) is significantly affected by video quality adaptation according to future network conditions for video streaming. In this paper, we jointly formulate D2D pair as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In the proposed scenario S2, the proposed method achieves a higher probability of ` using direct D2D mode than scenarios S1 and S3 due to the short distance between source and destination D2D pairs, and the low effectiveness of the cross-tier interference from the gNB. When the number of pairs ranges (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), scenario S3 shows better performance than proposed scenario S1 due to the proximity of D2D pairs. Scenario S1 outperforms scenario S3 when the number of pairs ranges (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) because of the severe cross-tier interference between D2D pairs in the proposed scenario S3.…”
Section: Table I Simulation Parametersmentioning
confidence: 90%
See 1 more Smart Citation
“…In the proposed scenario S2, the proposed method achieves a higher probability of ` using direct D2D mode than scenarios S1 and S3 due to the short distance between source and destination D2D pairs, and the low effectiveness of the cross-tier interference from the gNB. When the number of pairs ranges (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), scenario S3 shows better performance than proposed scenario S1 due to the proximity of D2D pairs. Scenario S1 outperforms scenario S3 when the number of pairs ranges (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) because of the severe cross-tier interference between D2D pairs in the proposed scenario S3.…”
Section: Table I Simulation Parametersmentioning
confidence: 90%
“…Simulation demonstrated that the suggested method had better performance in enhancing the overall system throughput. In [26], the authors presented methods dealing with resource allocation and pair association within the context of the D2D communication network. The issue of association in the D2D context has been defined as a one-to-one matching game and has been solved using the Gale-Shapley algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…According to future network requirements for video streaming, the quality of experience (QoE) is strongly influenced by video quality adaptation. Therefore, a new quality adaptation technique was proposed for scalable video in D2D communication network [13]. In addition to an extensive survey, a discussion on video transmission and QoE was conducted in studies [59], [60], which handled challenges and proposed possible solutions to enhance the video quality and manage interferences between cellular links and D2D links.…”
Section: B Video Streamingmentioning
confidence: 99%
“…According to the current and expected requirements of communication networks, an emerging technology called device-to-device (D2D) communication has attracted attention as a critical key for cellular network performance enhancement in 5GB [13], [14]. D2D communication offers many advantages for cellular networks, namely; (i) higher transmission rate, (ii) enhancing energy efficiency, (iii) offloading the overloaded cellular traffic, (iv) wide cellular coverage, (v) reducing delay or latency, and (vi) higher spectral efficiency [15]- [18].…”
Section: Introductionmentioning
confidence: 99%
“…The number of connected devices, especially, Internet of Things, is expected to be about 19.1 billion in the year 2025 and 29.4 billion in 2030 [1], [2] and [3], in which mobile data traffic is expected to advance from 13.8 in 2017 to about 110 Exabytes until the end of 2023, which represents a compound annual growth rate of 42% according to the Ericsson mobility report [4]. To meet all the expected needs for wireless communication networks, a promising technology labeled Device-to-Device (D2D) communication is emerging as a crucial key for wireless cellular network achievements improvement in 5G [5], [6]. D2D communication provides many merits for cellular networks, specifically: (i) high data transmission rate, (ii) energy efficiency enhancement, (iii) extended cellular coverage, (iv) support the overloaded cellular traffic, (v) latency reduction, and (vi) spectral efficiency improvement [7].…”
Section: Introductionmentioning
confidence: 99%